Current Trends in the Acceptance of Refugees by their Chosen Host Countries Globally - Sani , Standa; Murairwa, Stanley; Raissa, Nomel; Ndlovu, Nobesuthu T. (Lighthouse: The Zimbabwe Ezekiel Guti University Journal of Law, Economics and Public Policy, 2023)
Refugees and asylum-seekers face various obstacles in their quest for refuge in destination countries of their choice. These include dangerous border crossings and the possibility of being exploited by criminals. For refugees in particular, state-initiated barriers also take the form of restrictive immigration control measures once the refugees and asylumseekers have landed in the foreign countries of their choice. Because of such measures, refugee and asylum petitions are not processed expeditiously as most industrialised countries tighten their borders to pass off asylum-seekers to their neighbours. Restrictive immigration control measures are now the developed world‘s primary and, some might argue, sole response to the growing number of refugees and asylum-seekers. Addressing the existing unequal distribution of responsibility for and protection of refugees should be a fundamental component of immigration control measures. Greater commitment to multilateralism should be based mostly on sharing responsibility for refugees, through relocation, humanitarian visas, or regional and international distribution systems, and the sharing of resources such as emergency assistance, specialised personnel, expertise and funding.